METHODOLOGY FOR THE USE OF NON-TRADITIONAL PICTORIAL ACTIVITIES FOR CHILDREN AGED 5-7 YEARS - Aziza Yusupova (Web of Journals Publishing, 2024)
In this article, in order to expand the role of painting classes in non-traditional ways in fine arts classes in preschool educational organizations, to enrich children's creative thinking, to revive new views on life, to expand opportunities to enjoy what they are doing, to more effectively organize the visual activities carried out in preschool educational organizations with the help of children's capabilities It is about filling the country with diversity based on innovative technologies, developing children's self-confidence, teaching creative skills in a new direction using jajji fingers.
Keywords: Education, upbringing, development, movement, innovative ideas, innovative technologies, children's creativity, new world experiences, cooperation, solidarity issues.